Searches for scalar quarks in e+e- interactions at √s =189 GeV - Dova, María Teresa (1999)
Searches for scalar top and scalar bottom quarks, as well as for mass-degenerate scalar quarks of the first two families are performed at 189 GeV centre-of-mass energy with the L3 detector at LEP. No signals are observed. Model-independent limits on the scalar top production cross sections are determined for the decay modes <mtext>t</mtext><mtext>̃</mtext>1<mtext>→</mtext><mtext>c</mtext><mtext>χ</mtext><mtext>̃</mtext>10 and <mtext>t</mtext><mtext>̃</mtext>1<mtext>→</mtext><mtext>b</mtext><mtext>ℓ</mtext><mtext>ν</mtext><mtext>̃</mtext>. For scalar quarks of the other flavours <mtext>q</mtext><mtext>̃</mtext><mtext>→</mtext><mtext>q</mtext><mtext>χ</mtext><mtext>̃</mtext>10 decays are considered. Within the framework of the Minimal Supersymmetric Standard Model mass limits are set at 95% C.L. for these particles. Indirect limits on the gluino mass are also derived.